Gordança: celebrating fat bodies in dance from the south of the world (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The article reflects on issues that mobilized the creative process of Gordança: uma palestra dançada (2023), identifying the challenges and violences that fatphobia and aesthetic pressure impose on contemporary society, and, more specifically, on the very existence of fat dancers. To this end, the relationships between coloniality, capitalism and fatphobia are explored, through the recognition of their legacies and locations.  From the south of Brazil, from the perspective of artistic research, the work problematizes body patterns and affirms the need to celebrate diversity, including the curves and movements of fat women who dance.
Keywords: gordança; dance; fatphobia; fat body; performing Arts